Charles S. Peirce’s Centenary (1839-1914): Anti-nominalism, Judgment, and Religion - de Waal, Cornelis de Waal; Mayorga, Rosa M.; Nubiola, Jaime (Acta Philosophica, 2014)
Cornelis de Waal, Charles S. Peirce on Science, Religion, and God Rosa M. Mayorga, Peirce’ s anti-nominalism Jaime Nubiola, La relación de Charles S. Peirce con John H. Newman